Heart transplantation in patients with ventricular assist devices: Impacts of the implantation technique and support duration. Issue 2 (5th December 2019) - Immohr, Moritz Benjamin; Mehdiani, Arash; Albert, Alexander; Boettger, Charlotte; Dalyanoglu, Hannan; Scheiber, Daniel; Westenfeld, Ralf; Aubin, Hug; Lichtenberg, Artur; Akhyari, Payam; Boeken, Udo
Abstract: Background: Orthotopic heart transplantation (HTx) is the gold standard treatment for patients with terminal heart failure. As donor organs are limited, patients are often on ventricular assist device (VAD) support before receiving HTx. We aimed to compare the outcome after HTx in patients with and without preoperative VADs as well as in patients who underwent different VAD implantation techniques. Methods: A total of 126 patients underwent HTx at our department between 2010 and 2019 and were retrospectively analyzed. While 47 patients underwent primary transplantation (No VAD), 79 were on VAD support. The preoperative and intraoperative parameters were comparable between the two groups. Results: VAD support significantly increased the HTx operation time (<0.0001), cardiopulmonary bypass time ( P  < .01), and warm ischemia time ( P  = .04). The ventilation time ( P  = .02), intensive care unit (ICU) stay ( P  = .01), and hospital stay ( P  = .02) were also significantly longer in VAD patients than in No VAD patients. Minimally invasive VAD implantation significantly reduced the requirement for perioperative blood transfusion ( P  = .01) and rethoracotomy ( P  = .01). Nonetheless, survival analyses did not show significant differences between the groups, but there was a trend of better results for the primary transplantation patients (30‐day survival: No VAD = 91.1%, VAD = 86.1%; n.s.). Conclusions: We observed significantly worse perioperative parameters in patients who underwent transplantation after the implantation of a VAD compared to those who underwent primary transplantation. Minimally invasive VAD implantation without full sternotomy decreased complications during the subsequent HTx. In patients who are dependent on temporary VAD support as a bridge to transplantation, we believe that minimally invasive implantation should be performed if possible.